The Role of Social Capital in Families of Different Religions in Salatiga City - Erika Tataung; Izak Y. M. Lattu; Sri Suwartiningsih (International Journal of Science and Society, 2022)
The purpose of this study is to analyze the role of social capital in families of different religions in Salatiga city. The social capital used is from Fukuyama's explanation of trust, norms, and networks. In this study the authors use a qualitative approach, namely, research whose results are in the form of words based on the results of observations and interviews with informants both from body language, behavior, expressions or speech. From the research results analyzed using Fukuyama's Social Capital theory, the results show that families of different religions can live in harmony and harmony because they play social capital, namely trust, norms and networking in family communication and interaction internally and in the surrounding or external environment.